Time data results. - Shuai Huang (60512) (2025)
Drivers often engage in aggressive behaviors during time-reduction-goal tasks without fully understanding the actual time saved. This study investigated how such goals influence driving behavior and perception. A total of 99 young male drivers initially completed a survey assessing their beliefs about time-saving performance. Of these, 32 were randomly selected to participate in real driving experiments under both time-reduction and control conditions. Heart rate (HR), skin conductance response (SCR), and driving data were collected. Afterward, the experimental results were shared with all 99 drivers who completed the initial survey, including the 32 experimental participants and 67 non-participants. All drivers then provided cognitive feedback. The findings indicated that: (1) 78% of drivers believed that aggressive driving reduced both traffic light-affected time (TLT) and non-traffic light-affected time (NTLT); (2) Time-reduction goals led to more frequent acceleration and deceleration, reducing total travel time primarily in NTLT segments, while TLT remained stable. HR and SCR showed no significant increase in anxiety; (3) After receiving feedback, 72.7% of drivers, including 85.2% of participants and 69.4% of non-participants, agreed that aggressive driving had limited impact on TLT and expressed a willingness to modify their behavior. This study revealed actual behavioral outcomes under time pressure, assessed the potential of cognitive feedback, and provided insights for promoting safer and more efficient driving.